2018
DOI: 10.3389/fmicb.2018.01293
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Screening of Thermophilic Bacillus Strains for Developing Plant Growth Promoting Consortium From Hot Spring of Leh and Ladakh Region of India

Abstract: In the present investigation, the main aim is to identify and characterize the potential drought tolerant plant growth promoting consortium for agricultural productivity. Three bacterial isolates were isolated from hot spring of Chumathang area of Leh district. Bacillus species (BHUJP-H1, BHUJP-H2, and BHUJP-H3) were done some biochemical tests including catalase, cellulase, amylase, indole-3-acetic acid, phosphate solubilisation, production of ammonia, siderophore, and hydrogen cyanide. Molecular characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 65 publications
1
23
0
1
Order By: Relevance
“…In our study, we isolated bacterial strains from hot springs, screened them for plant growth promotion properties, and applied them on charcoal rot susceptible soybean variety NARC-II to observe their effects on disease control by modulating ROS scavenging system in soybean plants. Plant growth promoting bacteria (PGPB) isolated from hot springs and their vicinities are reported to be efficient plant growth-promoting agents [37,38]. In this study, 20 bacterial strains were isolated.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we isolated bacterial strains from hot springs, screened them for plant growth promotion properties, and applied them on charcoal rot susceptible soybean variety NARC-II to observe their effects on disease control by modulating ROS scavenging system in soybean plants. Plant growth promoting bacteria (PGPB) isolated from hot springs and their vicinities are reported to be efficient plant growth-promoting agents [37,38]. In this study, 20 bacterial strains were isolated.…”
Section: Discussionmentioning
confidence: 99%
“…The cellulolytic enzymes work efficiently at temperatures around 50 • C and in some studies, even at higher temperatures (Baharuddin et al, 2016). Verma et al (2018) isolated the cellulase producing thermophilic Bacillus subtilis BHUJP-H1, Bacillus sp. BHUJP-H2, Bacillus licheniformis BHUJP-H3 from hot spring of Leh and Ladakh, indicates that these samples would provide bacteria inhabiting extreme environment, high temperature, and pressure tolerance (high altitude).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas have been widely reported as NFB of nonlegumes [38] , [39] . Previous studies have shown that plant growth promoting bacteria are able to not only fix nitrogen but also produce IAA and ACC deaminase [40] , [41] .…”
Section: Resultsmentioning
confidence: 99%